Targeting PI3K in Cancer: Any Good News? - Martini, Miriam; Ciraolo, Elisa; Gulluni, Federico; Hirsch, Emilio (Frontiers in Oncology, 2013)
The phosphatidylinositol 3-kinase (PI3K) signaling pathway regulates several cellular processes and it’s one of the most frequently deregulated pathway in human tumors. Given its prominent role in cancer, there is great interest in the development of inhibitors able to target several members of PI3K signaling pathway in clinical trials. These drug candidates include PI3K inhibitors, both pan- and isoform specific inhibitors, AKT, mTOR and dual PI3K/mTOR inhibitors. As novel compounds progress into clinical trials, it’s becoming urgent to identify and select patient population that most likely benefit from PI3K inhibition. In this review we will discuss individual PIK3CA mutations as predictors of sensitivity and resistance to targeted therapies, leading to use of novel PI3K/mTOR/AKT inhibitors to a more “personalized” treatment.